2003
DOI: 10.1097/01.rli.0000069790.89435.e7
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Three-Dimensional Contrast-Enhanced Blood Oxygenation Level-Dependent Magnetic Resonance Venography of Brain Tumors at 3 Tesla: First Clinical Experience and Comparison with 1.5 Tesla

Abstract: Acquisition of CE-MRV data at 3 T enables spatial resolution to be increased within the same measurement time and with the same volume coverage compared with 1.5 T, thus providing more detailed information. The method may also show the potential to estimate oxygen supply of tumors, especially at high field strengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 24 publications
0
54
0
Order By: Relevance
“…It was previously shown that SWI works very well at 3T and even 4T (8,29). At 3T, for example, in the same period of time one could theoretically double the current coverage at Figure 7.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It was previously shown that SWI works very well at 3T and even 4T (8,29). At 3T, for example, in the same period of time one could theoretically double the current coverage at Figure 7.…”
Section: Discussionmentioning
confidence: 92%
“…The internal architecture represents the ability of a sequence to show spatial signal heterogeneity within a lesion. The spatial signal heterogeneity within a lesion is thought to represent tissue changes that are related to variance in structure and composition, and was previously described as being increased in SWI and phase imaging (8,23). Only low-signal structures that could be followed on contiguous images and had an apparently cylindrical structure were considered to represent veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SWI has been used as an MR venographic method for several years (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), it has more recently been applied to studies of arterial venous malformations (16,24), occult venous disease (15), multiple sclerosis (20), trauma (25), tumors (21,23,26), and functional brain imaging (14,22). Given the continued increasing clinical interest in this topic, it is important to ensure a complete understanding of the mathematical processes involved in creating SW images.…”
mentioning
confidence: 99%
“…HR-SW-MR imaging allows for noninvasive visualization of small veins in the human brain at submillimeter resolution and, therefore, is used to depict venous architecture in normal, as well as pathologic, tissue. [1][2][3][4][5][6][7][8] Because the underlying contrast mechanism is associated with the magnetic susceptibility difference between oxygenated hemoglobin (diamagnetic) and deoxygenated hemoglobin (paramagnetic), differences in the state of the blood oxygenation, such as in cerebral veins, result in differences in the bulk magnetic susceptibility of blood (static BOLD effect).…”
mentioning
confidence: 99%